Optimizing Asset Recovery in Corruption Cases: Evaluating Indonesia’s Legal Framework and the Need for Non-Conviction Based Forfeiture - Marlina Samosir; Raymundus Loin (al-Battar: Jurnal Pamungkas Hukum, 2026)
Corruption is categorized as an extraordinary crime that causes great losses to state finances, so it is not enough to overcome it only through corporate criminalization, but must also be oriented towards asset recovery. This study aims to analyze the effectiveness of the asset forfeiture mechanism in corruption crimes based on laws and regulations in Indonesia and identify the urgency of legal reform to increase the optimization of asset returns. This research uses a normative legal method with a statute approach and a conceptual approach. The data used is secondary data consisting of primary legal materials in the form of laws and regulations, such as the Criminal Code, Law Number 31 of 1999 jo. Law Number 20 of 2001, as well as Law Number 1 of 2023, and secondary legal materials in the form of scientific literature and legal doctrine. Data analysis was carried out qualitatively by examining the conformity of legal norms with the principle of effectiveness in recovering state losses. The results of the study show that the asset forfeiture mechanism in Indonesia's positive law is still dominated by the conviction based forfeiture model which depends on the main criminal verdict. This condition creates various limitations, such as a high burden of proof, a long process, and a legal loophole for perpetrators to hide or transfer assets resulting from corruption. As a result, the effectiveness of recovering state losses has not been optimal. Thus, legal reform is needed through strengthening asset forfeiture regulations, including the development of a non-conviction based asset forfeiture mechanism, in order to increase the effectiveness of asset recovery and strengthen efforts to eradicate corruption in Indonesia.